MoU: UiTM & Rukmini Devi Institute of Advanced Studies - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
UiTM Kedah and Rukmini Devi Institute of Advanced Studies officially signed a Memorandum of Understanding MoU to Strengihen Academic Collaboration and Foster Global Partnership. Even Held Vibrantly 1st August 2024.